Nueva sede de la universidad nacional de música en el distrito de Callao con el énfasis de arquitectura sensorial - Bustamante Villanueva, Adrian Aaron (2023)
The present research work aims to design a music university through different lineaments that comprise it. Initially, the problem of why this project is necessary for the conservation and reinforcement of the importance in the cultural-musical sector is determined, in addition to the fact that there is no educational institution of university music in the country that has been designed from a principle for such a function. Later on, the place of the Callao district to intervene and its purpose is determined, as well as the emphasis on Sensorial Architecture that will be used in order to reinforce the creative process of the artist - musician through concepts such as light, color, scale and landscaping, emphasizing the development and design of environments. Next, various referential projects corresponding to the selected typology are analyzed for the knowledge of the technical, environmental, architectural, technological and emphasis aspects in order to fully understand said university educational institution, as well as its theoretical study and international and national history. Finally, the normative criteria that must be followed and taken into account for the execution and design of the project are established through regulations, laws, treaties, among others.